2006
DOI: 10.1103/physrevlett.97.155503
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Method to New Phases of Polymeric Nitrogen under High Pressure

Abstract: A systematic method to unravel a large class of single-bonded (SB) polymeric phases of nitrogen under high pressure is presented. The approach is based on the combinatorial generation of different Peierls-like distortions of a given reference structure that maintain the threefold connectivity of SB nitrogen, followed by first-principles calculations. Using an eight atom simple cubic reference structure, the approach not only recovers all four SB nitrogen phases reported to date, but eight new metastable struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 19 publications
0
49
0
Order By: Relevance
“…Moreover, after chemical reaction, these systems decompose into nitrogen gas, which is environmentally safe. A few forms of polymeric nitrogen have been predicted theoretically, [4][5][6][7][8][10][11][12] and one of them, the cubic gauche form, has already been experimentally demonstrated. 2 Unfortunately, none of them are stable at ambient conditions of the temperature and pressure.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, after chemical reaction, these systems decompose into nitrogen gas, which is environmentally safe. A few forms of polymeric nitrogen have been predicted theoretically, [4][5][6][7][8][10][11][12] and one of them, the cubic gauche form, has already been experimentally demonstrated. 2 Unfortunately, none of them are stable at ambient conditions of the temperature and pressure.…”
mentioning
confidence: 96%
“…1,2 However, there are continuous efforts searching for metastable polymeric nitrogen or polynitrogen. [2][3][4][5][6][7][8][9][10][11][12] These materials contain single N-N and double N N bonds, which have large energy difference compared to N≡N triple bond. Once the single (double) bonded nitrogen transforms to N 2 molecule, a large amount of energy is released.…”
mentioning
confidence: 99%
“…Recent work on N 2 and H 2 has focused particular attention on the role of structure in facilitating transitions to nonmolecular and metallic phases at ultra-high pressure. A polymeric form of N 2 has been observed above 100 GPa and at high temperature, and may be an ideal highenergy density material if recoverable at ambient conditions [3][4][5][6] . In addition, metallic H 2 is expected to demonstrate near roomtemperature superconductivity and would represent the ultimate hydride, but has thus far eluded experimental efforts 7,8 .…”
mentioning
confidence: 99%
“…A systematic approach to search for new phases of single-bonded polymeric nitrogen at high pressure is outlined in [47]. It is reported that, along with the already known forms (Cg, BP, A7, and LB -the gauche structure, black phosphorus, arsenic, and layered boat structures) of polymeric nitrogen, this approach makes it possible to calculate the structures of eight more new metastable forms of single-bonded nitrogen.…”
Section: Theoretical Studiesmentioning
confidence: 99%